Efforts of Community Adaptation to Deal with Rob Floods on The Meulaboh Coastline - Febrianti, Dian; Zakia, Zakia; Safriani, Meylis; Ikhwali, M. Faisi; Husaini, Muhammad Zakki; Prayogo, Wisnu; Ersa, Nanda Savira; Farizal, Teuku (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
Most of Indonesia's territory is geographically located in the coastal area. One of the areas located in the coastal area is the city of Meulaboh, West Aceh Regency. The coastal area of Meulaboh often experiences tidal flooding, especially the coastal area of Gampong Pasir and has a quite severe impact compared to other areas on the coast of Meulaboh. Based on this background, this study aims to identify community adaptation to the tidal flood event based on community responses in the coastal area and identify efforts to mitigate the impact of tidal floods that have been carried out by the community and the government. The analytical methods used are descriptive quantitative and qualitative analysis methods, as well as cross-tabulation analysis related to community adaptation variables, which include community characteristics, the impact of tidal floods on the residential environment, identification of tidal flood conditions and efforts to mitigate the impact of tidal floods, carried out by the community and the government. The results showed that the people of the coastal area of Meulaboh were able to make efforts to deal with tidal floods in the form of repairing road networks, residential houses, drainage channels, places of worship (mosques), village offices, and clean water and sanitation systems. The government's efforts to deal with tidal floods are carried out by making barriers to protect the coast through tetrapod. These results are important to take future action to deal with tidal floods.